The determinants of decision-making in alcoholic patients - Fralova, Yuliya G.; Lado, Anastasia V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The paper describes the determinants of decision-making in alcoholic patients. Although voluntary attention deficit grows with development of alcoholism, this indicator, as well as the years of disease, was unrelated to the successful performance of Gambling Task. The only significant factor predicting scores in this task is the level of the patient’s impulsivity. The results obtained support Cognitive-motivational Theory of Personality Vulnerability to Alcoholism (P. R. Finn).
Keywords: alcohol dependence; decision-making; situation of uncertainty; Gambling Task; impulsivity; self-regulation of behavior